Kemiripan dan Evaluasi Produksi Aksesi Kenikir (Cosmos caudatus Kunth.) dari Jawa Barat - Jatsiyah, Venti; Susila, Anas Dinurrohman; Syukur, dan Muhamad (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2016)
ABSTRACTKenikir (Cosmos caudatus Kunth.) is an Indonesian indigenous vegetable which is potential to be developed. Exploration conducted in Bogor, Sukabumi, Bandung, Bandung Barat, Subang, Garut, Majalengka, Kuningan, and Tasikmalaya had succesfully collected 20 accessions of Cosmos sp. The objectives of this study were  to observe similarity and estimate the yield of Cosmos accessions from West Java. Clusters analysis grouped 20 Cosmos accessions into three clusters. Cluster I consisted of Pendeuy, Saribakti, Karang agung, Sindangbarang, Langensari, Perbawati, Sudajaya girang, Karang tengah, Argalingga, Warnasari, Sukaresmi, Ciwidey, Jalan cagak, Lebaksiuh, Tugu selatan, Ciwarak, Linggarjati and Babakan accessions. Cluster II and III consisted only one accession each which were Ciaruteun and Dramaga, respectively. Seven accessions from different sub cluster were evaluated to estimate the yield. A significant variability was found among the accessions. Results showed that those accessions were significantly different on plant height, stem girth, numbers of primary branches, number of leaf, leaves width, leaves length, days to flowering and yield. The results showed that Dramaga and Ciaruteun acessions were recomended to be developed because of its high yield. Keywords: characterization, cluster analysis, exploration